Rancang Bangun Alat Bantu Fiksasi dengan Penanda Waktu Eksposi Untuk Pemeriksaan Radiografi Abdomen Akut - Siti Masrochah; Yeti Kartikasari; Bagus Abimanyu (Jurnal Imejing Diagnostik (JImeD), 2015)
Backgroud: Limitations in a radiographic projection of the Left lateral decubitus (LLD) ussually challanges most of the Radiografers who intent to apply the technique toward patients with acute abdoment clinical cases. Related problems that occasionally come up with the LLD projection are the fixed patient positioning and the waiting time it takes to keep patient in the same position. The poor quality of  the LLD radiograph and less imaged optimalisation of the free-air below the right diapragm lead to a dificult radiological interpretation. The study aims to design an aided patient fixation tool with its controlling timer used for the LLD projection; and to examine the the functional performance of the tool.Methods: the research is qualitative approached with an experimental study. Several steps following the reseach are creation of the master plan designs and selection of materials that  should be used to develop an appropriate aided patient fixation tool with controlling timer for LLD projection; evaluation of the 5 designed tool system components (seated patient, cassette holder, safety belt, electronic sensored movement, andthe timer); and qualitative testing of the tool function and veryfication. The 6 aspects of tool performances have been decided to be complianced indicators whereas 5 observers (expert Radiographers) blended in the evaluation of the aided tool, and the tool has firmed to meet its requirement if the total observer’s score is greater and equal to 2,00Results: In general, the resulted tool perfomance testing fulfilled the requirements of the tool functions as it used for some radiographic procedures of the acute abdoment-LLD projection. The tool performance scores of convenince and reliability equipment showed at 2,25 and 2,75 which meant that a general radiographic quality was looking good without any presense of the artifacts. Morover, the scores for timer and censored devices were 2,70 and 2,65 recpectively, by this clearly described  a proper function of timer control and indicator components. The total score for radiation safety evaluation contributed to the higest score amongst all aspects being assessed that was 2,80.Conclusion: The design of the aided patient fixation tool with controlling timer for LLD projection has not only met functional requirements but it has also proven to subtitute some limitations about maintaning good image quality when applied the LLD projection. Radiologic expertation on the LLD-radiograph of the acute abdoment obviously contributed to optimal clinical information